Sub-lethal Responses of the Polychaete Armandia agilis in Whole-sediment Toxicity Testing - da Silva Toscano Saes, Renan Vandre; Moreira, Lucas Buruaem [UNESP]; Peres, Tiago Farias; Taniguchi, Satie; Bícego, Marcia Caruso; Marins, Rozane Valente; de Souza Abessa, Denis Moledo [UNESP] (Springer Nature, 2019)
The present study assessed biochemical responses as sublethal endpoints in the polychaete Armandia agilis exposed to contaminated sediments to in order to assess its potential use as a test organism. Sediment samples from several locations at a dredging site were obtained and used in whole-sediment exposures. Samples were tested with A. agilis to determine the 10-day toxicity of the 100% sample and the enzymatic activity of catalase (CAT), glutathione-S-transferase (GST) and acetylcholinesterase (AChE) biochemical measurements made in whole-body homogenates of a subset of the surviving organisms. Biochemical responses reported in A. agilis were not statistically different from the reference site sediment, however, the integrated analysis demonstrated that contaminants bound to sediment samples influenced the sublethal effects.
Keywords: Annelida; Benthic organisms; Biomarkers; Dredging; Environmental monitoring; Test organism